Предмет: Физика,
автор: telefonnnt
Помогите с задачей пожалуйста
Приложения:
Ответы
Автор ответа:
0
m1 * a = T - m1 * g
m2 * a = m2 * g - T
a * (m1 + m2) = g * (m2 - m1)
a = g * (m2 - m1) / (m1 + m2)
a = 10 * (0,3 - 0,2) / (0,3 + 0,2) = 2
s = a * t * t / 2
s = 2 * 1 * 1 / 2 = 1
m2 * a = m2 * g - T
a * (m1 + m2) = g * (m2 - m1)
a = g * (m2 - m1) / (m1 + m2)
a = 10 * (0,3 - 0,2) / (0,3 + 0,2) = 2
s = a * t * t / 2
s = 2 * 1 * 1 / 2 = 1
Приложения:
Автор ответа:
0
спасибо большое !
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Немецкий язык,
автор: zakazobed2010
Предмет: География,
автор: daniel7816
Предмет: Математика,
автор: Аноним